Letter to the Editor: COVID-19 Infections Do Not Change with Increasing Altitudes from 1,000 to 4,700 m - Castagnetto Mizuaray Jesus Martin (2020)
Coronavirus disease (COVID-19) infection, after the first case reported in Wuhan, China, on December 31, 2019 and declared a pandemic by the World Health Organization in March 2020, has climbed by September 2nd to 26,076,572 cases and 864,162 deaths worldwide. Although it has been suggested that living at high altitude could decrease the rate of coronavirus transmission and mortality from COVID-19 (Arias-Reyes et al., 2020), new studies have not confirmed this protective effect. In fact, the case–fatality rate in Peru did not change with altitude (Segovia-Juarez et al., 2020).